ULTRASOUND ASSISTED GREEN SYNTHESIS OF 2-FURAN-2-YL-4H-CHROMEN-4-ONES FROM CHALCONES - KAKADE, GOPAL K.; VEDPATHAK, SURESH G. (International Journal of Current Pharmaceutical Research, 2020)
Objective: To report the ultrasound-assisted synthesis of some bioactive 2-furan-2-yl-4H-chromen-4-one derivatives Methods: Oxidative cyclization of chalcones using iodine in dimethyl sulfoxide for the synthesis. Results: Some bioactive 2-furan-2-yl-4H-chromen-4-one derivatives were synthesized from corresponding chalcones in the presence of iodine in dimethyl sulfoxide under ultrasound irradiation at ambient reaction conditions. Conclusion: The use of ultrasound irradiation gave the advantages of higher yields, lower reaction time and simplicity compared to conventional methods for the synthesis of 2-furan-2-yl-4H-chromen-4-one derivatives.